Treatment of dermal varicose veins - Gomez Fossati, Carlos; Mazza Bruno, Milton; Sanguinetti, Julio; Mate, Miguel; Del Campo, Alberto; Bayardo, Gladys (Cirugía del Uruguay, 1971)
The revision of the most important clinical aspects of the disease is followed by a description of the different therapeutic methods applicable to dermal variculae or skin telangiectasis, with the indications and techniques of each. The paper also includes the results of the authors experience, on this subject, based on three years work in a phlebologic polyclinic of an obstetrics service.